2011
DOI: 10.1038/jhh.2011.93
|View full text |Cite
|
Sign up to set email alerts
|

Renal resistive index and low-grade inflammation in patients with essential hypertension

Abstract: In essential hypertension, increased renal resistive index (RRI) is associated to a reduction of renal function and microalbuminuria, and to renal tubulo-interstitial damage. A tubulo-interstitial inflammatory infiltration was found in experimental models of hypertension, and serum high-sensitive C-reactive protein (hsCRP) levels correlated with urinary markers of tubulointerstitial damage in humans. We studied the relationship between RRI and serum hsCRP in hypertensives with preserved renal function, without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In HT patients, involvement of glomerular vascular structures is characterized by albumin excretion. 27,28 In their study, € Ozelsancak et al 27 reported higher levels of RRI in non-treated hypertensive patients compared to the control group. Again in the same study, a positive correlation between RRI and urinary albumin excretion, and a negative correlation between RRI and creatinine clearance was reported.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In HT patients, involvement of glomerular vascular structures is characterized by albumin excretion. 27,28 In their study, € Ozelsancak et al 27 reported higher levels of RRI in non-treated hypertensive patients compared to the control group. Again in the same study, a positive correlation between RRI and urinary albumin excretion, and a negative correlation between RRI and creatinine clearance was reported.…”
Section: Discussionmentioning
confidence: 91%
“…It has a critical role in evaluating blood flow in renal artery and vein pathology (such as stenosis, thrombosis, and trauma), acute and chronic renal inflammation, and parenchymal pathology. 8,19 RRIbased studies on patients with systemic lupus erythematosus (SLE), 20,21 scleroderma patients, 22,23 diabetic patients, [24][25][26] and hypertensive patients 27,28 are available in the literature. SLE is another autoimmune connective tissue disease that may cause kidney involvement.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Berni et al [10], the proportion of patients having RRI ≥0.70 was found to be about 25%. <precision/absolute error was kept at 5% and type 1 error was kept at 5%.…”
Section: Methodsmentioning
confidence: 99%
“…Increased intrarenal RI is considered a marker of intrarenal arterial stiffness and is associated with the worsening of renal function and tubulointerstitial damage related to the inflammatory status of the essential hypertension: in humans, high-sensitivity C-reactive protein (hs-CRP) serum levels correlate with urinary markers of tubulointerstitial damage, and in hypertensive patients, the hs-CRP value directly correlates with the RI. 21 The most common cause of renovascular hypertension is the renal artery stenosis (RAS) owing to atherosclerotic disease. In these patients, renal intraparenchymal RI has been proven to be higher than in the cases of RAS induced by Takayasu's arteritis or fibromuscular dysplasia, because, in atherosclerotic patients, arteriosclerosis, intrarenal arteriolosclerosis and glomerular sclerosis are associated with an increase in vascular stiffness, a reduction in arterial compliance and inward remodelling of the RA.…”
Section: Parenchymal Nephropathiesmentioning
confidence: 99%